2014
DOI: 10.1186/2193-1801-3-107
|View full text |Cite
|
Sign up to set email alerts
|

Hernioplasty and testicular perfusion

Abstract: Open and laparoscopic tension-free techniques of hernia repair using synthetic meshes are a well-accepted practice with an excellent patient comfort and a low recurrence rate. It is well known that, direct contact of the mesh to the vessels in the inguinal canal and perimesh fibrosis may have a negative impact on testicular flow. Whether different operative techniques or mesh materials used have an effect on the integrity of the testicle, the influence of the resulting fibrosis on testicular perfusion, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…21 Also, extensive fibrosis after mesh implantation leads to nerve entrapment and chronic pain. 22 So the surgeons should prefer tissue based techniques when dealing with a young patient. The absence of severe adverse events in this study demonstrates that both Desarda and Lichtenstein methods can safely be employed in day care surgery.…”
Section: Discussionmentioning
confidence: 99%
“…21 Also, extensive fibrosis after mesh implantation leads to nerve entrapment and chronic pain. 22 So the surgeons should prefer tissue based techniques when dealing with a young patient. The absence of severe adverse events in this study demonstrates that both Desarda and Lichtenstein methods can safely be employed in day care surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search carried out by Dilek found that there was no difference in testicular blood flow after open or laparoscopic inguinal hernia surgery 14. However, Gurbulak et al found that although all parameters (PSV, EDV, and RI) were affected in the early postoperative period, they all returned to initial levels during the late postoperative period 5.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preservation of testicular vascularity is another issue of importance [6]. Hernia recurrence is attributed mostly to overlooking spermatic adhesion or extraperitoneal fat attached to the internal ring [7].…”
Section: Introduction and Review Of Surgical Technique Conceptmentioning
confidence: 99%